Strategi Komunikasi Branding Pariwisata Halal Berbasis Smart Tourism di Tana Toraja - Artianasari, Nining; Nurhakki; Musmuliadi (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2024)
The natural charms of Tana Toraja and North Toraja districts have grown into world tourism magnets. Tana Toraja attracts many tourists because of its peculiarities and attractive destinations, such as cultural natural and sports tours